Keberadaan Bumdes Sebagai Institusionalisasi Struktur Ekonomi Desa (Studi di Desa Grenden, Puger Kabupaten Jember) - Okta Deviya Devi (Universitas Islam Nahdlatul Ulama Jepara, 2021)
AbstractThe existence of Gunung Mulia Village-Owned Enterprises (BUMDes) in Grenden Village, Puger District, Jember Regency, provides an economic contribution whose strength is tremendous in improving the economy of the village community. This BUMDes is one of the village institutions which is engaged in the economic, social and cultural fields that accommodates the aspirations of the community which are then used in planning for development. Both economic, social and cultural development. The existence of BUMDes which certainly plays an important role in the village economy, of course every activity carried out is appreciated and fully supported by the community. The existence of BUMDes itself has been regulated in law and is indeed an institution from the village, but its management is separated by the village so that BUMDes has its own work plans and programs in developing the economy and increasing the potential of the village which later aims to create an independent village. The economic activities carried out by BUMDes include the creative economy by developing the potential of the village such as the existence of UMKM or the Sore Market, and working with various parties to create new economic activities, and other activities related to non-economics, namely moving in the cultural field. This economic institution is a form of institutionalization of the economic structure in the village with various changes in various aspects of community life.Keywords: creative economy, economic cooperations, regional autonomy, village institutions, village-owned enterprisesAbstrakKeberadaan Badan Usaha Milik Desa (BUMDes) Gunung Mulia yang berada di Desa Grenden Kecamatan Puger Kabupaten Jember memberikan sumbangsih ekonomi yang kekutannya sangat luar biasa meningkatkan perekonomian masyarakat desa. BUMDes ini merupakan salah satu lembaga desa yang bergerak dalam bidang ekonomi, sosial dan budaya yang menampung aspirasi masyarakat untuk kemudian digunakan dalam melakukan perencanaan dalam melakukan pembangunan . Baik pembangunan ekonomi, sosial serta budaya. Keberadaan BUMDes yang tentunya berperan penting dalam perekonomian desa tentunya setiap kegiatan yang dilakukan diapresiasi dan didukung penuh oleh masyarakat . Keberadaan BUMDes sendiri sudah diatur dalam hukum dan memang merupakan lembaga dari desa akan tetapi pengelolaannya terpisah oleh desa sehingga BUMDes memiliki rencana dan program kerja tersendiri dalam membangun perekonomian dan meningkatkan potensi desa yang nantinya bertujuan menciptkan desa yang mandiri. Kegiatan ekonomi yang dilakukan oleh BUMDes meliputi ekonomi kreatif dengan mengembangkan potensi dari desa tersebut seperti adanya UMKM atau Pasar Sore, dan bekerja sama dengan berbagai pihak untuk menciptakan kegiatan ekonomi baru, dan kegiatan lainnya berkaitan dengan non-ekonomi yakni bergerak dalam bidang budaya. Lembaga ekonomi inilah sebagai wujud dari institusionalisasi struktur ekonomi di desa dengan berbagai perubahannya di berbagai segi kehidupan masyarakat.Kata kunci: badan usaha milik desa, ekonomi kreatif, institusi desa, kerjasama ekonomi, otonomi daerah